Dark matter and the anthropic principle - Hellerman, Simeon; Walcher, Johannes (Physical review. D, Particles, fields, gravitation, and cosmology, 2005)
We evaluate the problem of galaxy formation in the landscape approach to phenomenology of the axion sector. With other parameters of standard ΛCDM cosmology held fixed, the density of cold dark matter is bounded below relative to the density of baryonic matter by the requirement that structure should form before the era of cosmological constant domination of the universe. Galaxies comparable to the Milky Way can only form if the ratio also satisfies an upper bound. The resulting constraint on the density of dark matter is too loose to select a low axion decay constant or small initial displacement angle on anthropic grounds.